Impacts of Development on Coastal Erosion - Nik Hassan, Nik Mohd Kamel; Hashim, Ahmad Mustafa; Sofian Tan, Iwan Tan (Earth Observation Centre (EOC), Universiti Kebangsaan Malaysia, 2009)
Malaysia’s coastal zone is experiencing stress due to development. Impact is not only a result of coastal development but also development carried out in the hinterland. Apart from degradation of water quality, erosion is a major impact problem on the shoreline. Coastal erosion induced by human activities has probably surpassed coastal erosion driven by natural factors. It is important to understand causes and impacts before prescribing any control measure. Depletion of coastal resources such as corals, marine flora and fauna and mangroves can be attributed to degradation of marine water quality. Adverse impacts of coastal erosion include destruction of assets located on retreating coastlines, undermining of coastal structures, loss of land of economic and ecological values and loss of habitats. Past measures to manage the problem have generally been designed from a local perspective. The implementation of a planning and management tool such as the Integrated Shoreline Management Plan (ISMP) shall provide appropriate measures in ensuring sustainable development in the dynamic coastal area. It provides a mechanism for decision makers to make rational and informed decision on coastal development, land use planning and erosion control measures.